A22. Clinical Topics in Lung Cancer 2009
DOI: 10.1164/ajrccm-conference.2009.179.1_meetingabstracts.a1104
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Planning Complexity and Survival after Treatment of Advanced Stage Lung Cancer in the Elderly.

Abstract: Purpose-Complex radiotherapy (RT) planning is increasingly common in the treatment of lung cancer though it remains unclear if these treatments are associated with better outcomes. We evaluated the association between the complexity of RT planning simulation with survival among elderly Stage IIIB non-small cell lung cancer (NSCLC) patients.Methods-We included all patients aged >65 years with histologically confirmed Stage IIIB NSCLC diagnosed between 1992 and 2002 receiving chemotherapy and RT from the Surveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Patients who received PORT were categorized accordingly if SEER codes indicated that they received postoperative external‐beam RT or if Medicare inpatient, outpatient, or physician claims contained any code indicating PORT use within 4 months of surgery 25. RT complexity was determined using planning and simulation codes from Medicare physician claims 26, 27. Postoperative receipt of chemotherapy (platinum‐based or other regimens) was determined from Medicare claims using published algorithms 28…”
Section: Methodsmentioning
confidence: 99%
“…Patients who received PORT were categorized accordingly if SEER codes indicated that they received postoperative external‐beam RT or if Medicare inpatient, outpatient, or physician claims contained any code indicating PORT use within 4 months of surgery 25. RT complexity was determined using planning and simulation codes from Medicare physician claims 26, 27. Postoperative receipt of chemotherapy (platinum‐based or other regimens) was determined from Medicare claims using published algorithms 28…”
Section: Methodsmentioning
confidence: 99%
“…The complex simulation and planning group consisted of patients who received complex planning and 3D simulation (CPT-4 codes: 77263, 77290, 77295, and 77301). Conversely, the intermediate simulation and planning group consisted of patients who underwent intermediate planning with intermediate simulation (CPT-4 codes: 77262 and 77285), which usually uses 2D planning software and standard 2D simulation systems 13. Finally, the simple simulation and planning group consisted of patients who received simple planning and simple simulation (CPT-4 codes: 77261 and 77280).…”
Section: Methodsmentioning
confidence: 99%